AKTIVITAS PENANGKAL RADIKAL BEBAS DAN PENSTABIL OKSIGEN SINGLET DARI EKSTRAK DAUN KUNYIT (Curcuma Domestica Val.) - Suryanto, Edi (CHEMISTRY PROGRESS, 2009)
The objectives of study was to determine free radical scavenging and singlet oxygen quenching (SOQ)activity in turmeric leaves extract. Analyses of phytochemicals were based on total phenolic, flavonoid andcondensed tannins. The radical scavenging activities of extracts were determined by 1.1-diphenyl-2-picrylhydrazyl (DPPH) assay. Turmeric leaves powder was extracted with methanol 80%, ethanol 80% danacetone 80% at room temperature for 24 hours, respectively. Singlet oxygen quenching (SOQ) activity ofeach tumiric leaves extracts at 500-1500 ppm level. SOQ activity test was conducted using linoleic acid assubstrates each containing 5 ppm erythrosine as a photosensitizer. The highest total phenolic flavonoidcontent was detected in methanol extract, followed by acetone extract and ethanol extract. Contrary,ethanol extract contained higher contents of condensed tannins than methanol extract and aceton extract.The addition of metanol extracts of turmeric leave in the reaction mixture showed the highest scavengingactivity in DPPH free radical followed by acetone extract and ethanol extract. The singlet oxygenquenching activities of turmeric extracts were greatly different in different solvents. The methanol extractexhibited the highest singlet oxygen quenching activities followed by acetone extract and ethanol extractunder fluorescent light for up to 5 hours. These result suggested that phenolic extract of turmeric leaveshad free radical scavenging and singlet oxygen quenching activitiesÂ Keywords : turmeric leaves, phenolic extract, free radical scavenging, singlet oxygenquenching